Educar para além das celas de aula: educação prisional como ferramenta de ressocialização - Santos, Molaynni Cerillo (2019)
This research seeks to reflect on the educational process and t consider possibilities of new practices for education in prisons focused at the resocialization of persons deprived of liberty, with the contribution of the subjects directly involved in the schooling process: managers, teachers and prisoners. To know these "looks", as a research tool, the semi-structured interview and focus group were used. Qualitative research was exploratory. In addition to the documentary analysis of the normative bases that deal with prison education, a field research was analyzed in the Xuri Penitentiary Complex (Complexo Penitenciário do Xuri), in Vila Velha-ES, which is the locus of the investigation. Education has a fundamental role in the process of individual’s resocialization, but education, to be efficient in its resocializing intent, it must be differentiated, especially in prisons. Prison education should be based on an intercultural pedagogy that enables the prisoner to (re) build and recognize himself as a subject of rights and practical education that enables the prisoner to duties before society; must be a be inserted in the labor market and thus have an alternative beyond crime, breaking the stigma that the prison is a school of crime. This research aims to understand how education should be offered in the prison area in order to enhance the resocialization of the individual.